Reward Learning, Neurocognition, Social Cognition, and Symptomatology in Psychosis - Lewandowski, Kathryn E.; Whitton, Alexis E.; Pizzagalli, Diego A.; Norris, Lesley A.; Ongur, Dost; Hall, Mei-Hua (Frontiers in Psychiatry, 2016)
Background: Patients with psychosis spectrum disorders exhibit deficits in social and neurocognition, as well as hallmark abnormalities in motivation and reward processing. Aspects of reward processing may overlap behaviorally and neurobiologically with some elements of cognitive functioning, and abnormalities in these processes may share partially overlapping etiologies in patients. However, whether reward processing and cognition are associated across the psychoses and linked to state and trait clinical symptomatology is unclear. Method: The present study examined associations between cognitive functioning, reward learning, and clinical symptomatology in a cross-diagnostic sample. Patients with schizophrenia (n=37), bipolar I disorder with psychosis (n=42), and healthy controls (n=29) were assessed for clinical symptoms (patients only), neurocognitive functioning using the MATRICS Battery (MCCB) and reward learning using the Probabilistic Reward Task (PRT). Groups were compared on neurocognition and PRT response bias, and associations between PRT response bias and neurocognition or clinical symptoms were examined controlling for demographic variables and PRT task difficulty (discriminability). Results: Patients with schizophrenia performed worse than controls on most measures of neurocognition; patients with bipolar disorder exhibited deficits in some domains between the level of patients with schizophrenia and controls. The schizophrenia – but not bipolar disorder – group exhibited deficits in social cognition compared to controls. Patients and controls did not differ on PRT response bias, but did differ on PRT discriminability. Better response bias across the sample was associated with poorer social cognition, but not neurocognition; conversely, discriminability was associated with neurocognition but not social cognition. Symptoms of psychosis, particularly negative symptoms, were associated with poorer response bias across patient groups. Discussion: Reward learning was associated with symptoms of psychosis – in particular negative symptoms – across diagnoses, and was predictive of worse social cognition. Reward learning was not associated with neurocognitive performance, suggesting that, across patient groups, social cognition but not neurocognition may share common pathways with this aspect of reinforcement learning. Better understanding of how cognitive dysfunction and reward processing deficits relate to one another, to other key symptom dimensions (e.g. psychosis), and to diagnostic categories, may help clarify shared etiological pathways and guide efforts toward targeted treatment approaches.